PERENCANAAN CAMPURAN BETON MENGGUNAKAN AGREGAT QUARY WAI-TUNSA DAN PERAWATAN DENGAN AIR LAUT DAN AIR TAWAR - Fara Dina; Selviana Walsen; Abraham Tuanakotta (Journal Agregate, 2022)
"Concrete Mix Design Using Quarry Wai-Tunsa Aggregates and Treatment Using Seawater and Freshwater". This thesis was under the guidance of Ms. Selviana Walsen and Mr. Abraham Tuanakotta.This study discusses the effect of aggregate due diligence on concrete mixtures and the effect of curing concrete using seawater and river water on the characteristics of concrete. Based on the conditions in the field, that development in the field of concrete construction used in the area uses more aggregates from rivers. The Wai-Tunsa River, which is one of the major and closest rivers in the area, is the main location for the community to collect aggregates and the Wai-Tunsa River has never been studied before on its aggregates. So that it still cannot be fully utilized, because it is not known for sure the level of its resistance when used as a concrete construction material.The purpose of this study is to explain the suitability of aggregate in concrete mixes and the effect of water type on variations in concrete curing using seawater and fresh water.In this study, Tonasa cement was used with a total of 2 immersion variations and 12 cylindrical specimens with a diameter of 15 cm and a height of 30 cm. The seawater immersion variation uses the same standard mix design as the freshwater immersion variation. Tests were carried out in the form of workability checks, compressive strength, and absorption values. Do the compressive strength results show that at the age of 28 days, all specimens treated with seawater were higher than concrete treated with river water with a value obtained for seawater-treated concrete of 25.66 N/mm? and the value obtained from fresh water-treated concrete is 25.10 N/mm.Keywords: compressive strength, seawater, treatment variation, Job Mix Formula